2018
DOI: 10.1021/acs.analchem.8b01143
|View full text |Cite
|
Sign up to set email alerts
|

A Ratiometric Fluorescent Bioprobe Based on Carbon Dots and Acridone Derivate for Signal Amplification Detection Exosomal microRNA

Abstract: Recently, sensitive and selective detection of exosomal microRNAs (miRNAs) has been garnering significant attention, because it is related to many complex diseases, including cancer. Herein, we report a ratiometric fluorescent bioprobe based on DNA-labeled carbon dots (DNA-CDs) and 5,7-dinitro-2-sulfo-acridone (DSA) coupling with the target-catalyzing signal amplification for the detection of exosomal miRNA-21. There was high fluorescence resonance energy transfer (FRET) efficiency between carbon dots (CDs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(68 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…For instance, a ratiometric fluorescent bioprobe based on DNA-labeled carbon dots (DNA-CDs) and 5,7-dinitro-2-sulfo-acridone (DSA) coupling with the target-catalyzing signal amplification for the detection of exosomal miRNA-21. There was high fluorescence resonance energy transfer (FRET) efficiency between carbon dots (CDs) and DSA when the bioprobe was assembled [ 81 ].…”
Section: Exosomal Mirna and Clinical Implicationsmentioning
confidence: 99%
“…For instance, a ratiometric fluorescent bioprobe based on DNA-labeled carbon dots (DNA-CDs) and 5,7-dinitro-2-sulfo-acridone (DSA) coupling with the target-catalyzing signal amplification for the detection of exosomal miRNA-21. There was high fluorescence resonance energy transfer (FRET) efficiency between carbon dots (CDs) and DSA when the bioprobe was assembled [ 81 ].…”
Section: Exosomal Mirna and Clinical Implicationsmentioning
confidence: 99%
“…However, the fluorescence of b-CDs was not quenched when the probe was used to detect PTK 7. As shown in Figure 3 meanwhile, would be reduced if there was an energy transfer [11,32] . The data in Figure 3(D) indicated that whether the fluorescence quenching behaviour of b-CDs by y-CDs disappeared or not was due to their separation.…”
Section: Scheme 1 Preparation Process and Ptk 7 Detection Mechanism mentioning
confidence: 99%
“…Carbon dots (CDs) are a new kind of fluorescence nanomaterial that have attracted wide attention owing to their excellent properties including good photostability, easy modification, stable chemical properties, favourable biocompatibility and excellent water-solubility [9,10] . CDs have been used to set up biosensors due to their excellent properties for metal ions, micromolecules and protein analysis [11][12][13] . Because of the relatively low concentration of PTK 7 in peripheral circulation, the biosensors for PTK 7 detection need to be equipped with high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical biosensor is a sensing platform that evaluates changes in electrical parameters (current, impedance, conductivity, voltage, or potential signal) through biochemical reactions between a biometric element and a target analyte [73]. Simple equipment, high sensitivity and easy miniaturization have always been the key research object of analytical researchers [74,75]. In recent years, electrochemical biosensors combined with nanomaterials have been vigorously developed because they can overcome the shortcomings of poor selectivity and low sensitivity in the original sensor detection methods.…”
Section: Metal Nanomaterials For Aflatoxins Detectionmentioning
confidence: 99%